Understanding web documents: finding pagelets for transformation using structural patterns. (16th July 2008) - Ferrydiansyah, Reza; Parmanto, Bambang
Understanding a web document and the sections inside the document is very important for web transformation and information retrieval from web pages. Detecting pagelets, which are small features located inside a web page, in order to understand a web document's structure is a difficult problem. Current work on pagelet detection focuses only on finding the location of the pagelet without regard to its functionality. We describe a method to detect both the location and functionality of pagelets using HTML element patterns. For each pagelet type, an HTML element pattern is created and matched to a web page. Sections of the web page that matches the patterns are marked as pagelet candidates. We test this technique on multiple popular web pages from the news and e-commerce genres. We find that this method adequately recalls various pagelets from the web page.